(untitled) (Eurasian Journal of Ecology, 2018)
This article deals with the accumulation of municipal solid waste. Using satellite images was analyzed the state of landfills for municipal solid waste in the suburban areas of Almaty city. Currently Kazakhstan pays much attention to waste management issues. One of the key directions of the Concept for transition the Republic of Kazakhstan to the “green” economy is the management of waste. According to the concept by 2030, the proportion of recycled waste should be 40%, and by 2050 – 50%. However, today within the Almaty city and its adjacent territories the number and variety of municipal solid waste (MSW) is rapidly increasing. At the same time, the organization of their utilization remains far from solved. Age of new technologies and industrial capabilities requires a essential solution of issues, transportation, processing and storage of these wastes. The problem of environmental hazards from the number and composition of municipal solid waste is highly discussed in Kazakhstan. This risk touch on all stages of municipal solid waste, starting with the collection and disposal of waste, completing with the preparation for usage of waste components and the destruction or burial of unused fractions. Until nowadays there is no uniform system of regulations for municipal solid and similar waste. One document define the conditions of handling of municipal solid waste, while the second ones – define industrial, medical, biological waste, and third ones – the production and consumption waste. It is still not defined the extent and danger of MSW class , depending on the content in their composition of toxic substances such as heavy metals (lead, cadmium, nickel, chromium, and others.), carcinogens and mutagens, pathogenic micro-organism and viable helmint eggs. In this situation, there are often raises notion that all problems related to MSW can solve modern Western development or, vice-versa, non-demanded unique domestic technology. In this regard, in order to solve the problems of accumulated rubbish, through the many dumping places , it is necessary to find out their actual current amount and to determine the occupied area under the rubbish. Everyday Almaty city produces 1,300 tons of waste, and nearly 200 tones of it collected from the streets. The bulk of generated municipal solid waste (MSW) is transported and stored at the territory of sites. During the year, there is typed more than 600 thousand tons of municipal waste. Totally there have already accumulated about 8 million tons of MSW. Currently, the city site, which is located in the Algabas village, exhausted its resource, as well as site, which is located in Karasai area. Therefore, in the suburban areas there are increasing the growth of natural garbage dump and municipal waste. Our only one rubbish recycling plant is not functioning, so the activities of organizations for depositing waste are not performed. All of collected waste is disposed on landfills of municipal solid waste, which are designated for these needs from the land fund of the Almaty region. The high density of population, a low percentage of recycling, low rates of penalties, poor organization of disposal and storage solid waste in Almaty city and suburbs of the metropolis have led to increase growth of dumping place. Key words: municipal solid waste, GIS technology, landfills, monitoring, rational distribution, system approach, space images.